Evaluation of serum leptin and adiponectin and their associations with obesity-related renal injury among Egyptian adolescents - Azza A El-Shaheed; Reham F. Fahmy; Nermine N. Mahfouz; Salwa R El-Zayat; Hiba Sibaii; Rehab S.I. Moustafa (Journal of the Arab Society for Medical Research)
Background/aim Childhood obesity has come to be a worldwide epidemic. Current epidemiological data advocate that obesity is linked with an increased threat of renal injury in children. Early markers will be beneficial in the prevention of renal injury. The present study aimed to assess serum levels of leptin and adiponectin and their associations with comorbidities of obesity to examine their potential effects on obesity-related renal injury among Egyptian overweight/obese adolescents. In addition, the study aimed an analysis of the kidney injury molecule-1(KIM-1) to identify the early renal effect of obesity. Subjects and methods A case–control study was conducted on 45 Egyptian overweight/obese adolescents aged 10–18 years of both sexes and 44 age- and Sex-matched healthy individuals. Serum fasting glucose and insulin were analyzed, and a homeostasis model assessment of insulin resistance was calculated. Serum leptin, adiponectin, and KIM-1 were measured using ELISA techniques. Results The overweight/obese group had significantly higher KIM-1 and leptin levels, and lower adiponectin levels in comparison to the control group (P=<0.05). Serum adiponectin levels had significant negative correlations, with both systolic (r=−0.480, P=0.013) and diastolic (r=−0.491, P=0.011) blood pressure, while serum leptin levels did not correlate with BMI, systolic blood pressure, diastolic blood pressure, HOMA- IR, eGFR, or KIM-1 in the study group (P>0.05). Conclusion Leptin and adiponectin are the main pathogenic factors for renal injury in obese adolescents.